2004
DOI: 10.1080/10715760410001705131
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Prevents Oxidative Stress and Hepatocyte Cell Death Induced by Experimental Cholestasis

Abstract: The induction of oxidative stress precedes liver injury during experimental obstructive jaundice (OJ). In this sense, different evidences suggest that melatonin (MEL), as antioxidant, may be useful in the protection against apoptosis and necrosis during experimental cholestasis. In addition, we will also assess if MEL-dependent protection is related to a recovery of antioxidant status disturbances induced by OJ. Cholestasis was achieved by double ligature and sectioning of the principal bile duct. MEL was inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
57
0
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 19 publications
8
57
0
5
Order By: Relevance
“…[21] TS'de MDA düzeyinin arttığı çeşitli çalışmalarla ortaya konulmuştur. [18,[22][23][24][25][26] LPO'da benzer şekilde hücre-sel hasara işaret eder. Beta glukanın sepsis, yanık gibi durumlarda ortaya çıkan karaciğer hasarını ve MDA seviyesini azalttığını bildiren yayınlar vardır.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…[21] TS'de MDA düzeyinin arttığı çeşitli çalışmalarla ortaya konulmuştur. [18,[22][23][24][25][26] LPO'da benzer şekilde hücre-sel hasara işaret eder. Beta glukanın sepsis, yanık gibi durumlarda ortaya çıkan karaciğer hasarını ve MDA seviyesini azalttığını bildiren yayınlar vardır.…”
Section: Discussionunclassified
“…TS'de, GSH'nin azaldığı birçok çalışmada gösterilmiştir. [22][23][24][25][26] Şener ve arkadaşlarının [29] çalışmasında, kronik nikotin uygulamasının etkilediği böbrek ve mesanede, doku GSH seviyelerinin düştüğü ve beta glukan verilmesinin doku GSH seviyelerini anlamlı olarak arttığı tespit edilmiştir. Toklu ve arkadaşlarının [30] çalış-masında, beta glukanın asetaminofen kaynaklı karaciğer toksisitesinde GSH düzeyini arttırdığı ve karaci- ğer hasarını azalttığı bildirilmiştir.…”
Section: Discussionunclassified
“…It has been found that melatonin has a higher antioxidant efficiency than vitamin E and GSH, which are known as powerful antioxidants [10] . The antioxidant properties of melatonin prevent acute liver injury induced by ischemiareperfusion [23] , irradiation [24] , bile duct ligation [25][26][27] , and toxins [18,28,29] . Several lines of evidence suggest that melatonin plays an important role in regulation of collagen levels and inhibition of collagen accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…2 Oxidative stress has an important role in hepatocyte cell death and hepatocellular injury during experimental induced cholestasis. 3 Actually, bile acids have been reported to stimulate the generation of reactive oxygen species in hepatocytes and liver mitochondria by their interference with mitochondrial electron transport chain. [4][5][6] Contrary to oxidative stress, the role of nitrosative stress in cholestatic liver diseases has received much less attention.…”
mentioning
confidence: 99%